Method for preparing adhesive-free artificial board from corn straw in environment-friendly mode

By separating and purifying lignin and cellulose from corn stalks, optimizing the ratio and using water as solvent for hot pressing, the environmental pollution and complex process problems caused by the use of organic solvents in the prior art are solved, and green and environmentally friendly The preparation of rubber artificial boards improves the mechanical properties and environmental value of the boards.

CN119260879APending Publication Date: 2025-01-07JIANGNAN UNIV +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411676749.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art uses a large amount of organic solvents in the preparation of plant straw glue-free plates, which has problems such as complex process flow, serious environmental pollution, and neglecting the impact of lignin and cellulose ratio on the performance of the board.

Method used

By separating and purifying lignin and cellulose from corn stalks, optimizing their ratio, and using water as the only solvent, gum-free artificial boards were prepared by hot pressing to achieve green preparation, and wastewater was carried out through chromatography separation and membrane separation systems. Recycling.

Benefits of technology

It has achieved green and environmentally friendly production of glue-free artificial boards, reduced production costs, improved the mechanical properties and environmental value of the boards, and is suitable for application scenarios with high environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147224530000061
    Figure BDA0005147224530000061
  • Figure BDA0005147224530000071
    Figure BDA0005147224530000071
  • Figure HDA0005147224550000011
    Figure HDA0005147224550000011
Patent Text Reader

Abstract

The invention belongs to the technical field of straw comprehensive utilization, and particularly relates to a method for green preparation of a glue-free artificial board from corn straw. The method comprises the following steps: separating and purifying lignin and cellulose from corn straws; then, the ratio of lignin to cellulose is optimized, water serves as a unique solvent, and the artificial board is prepared in a green mode in a hot press forming mode. Compared with the prior art, no external adhesive or modified chemical reagent needs to be added in the preparation process of the adhesive-free artificial board, lignin and cellulose in the corn straw are extracted and separated, then the ratio of lignin to cellulose is optimized, water is used as a unique solvent, and the adhesive-free artificial board is prepared. The glue-free artificial board can be prepared in a wide temperature range through hot pressing. The prepared adhesive-free artificial board has the characteristics of low production cost, no pollution of biological materials and the like. The density of the prepared non-adhesive plate can reach 0.69 g cm <-3 >, and the elastic modulus is 1035 MPa. The board is expected to become a substitute of a traditional board and has important significance on comprehensive utilization of the corn straws.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of comprehensive utilization of straws, and in particular relates to a method for greenly preparing glue-free artificial boards from corn straws. Background Art

[0002] Corn stalks are one of the agricultural residues, which are rich, cheap, safe and renewable. They contain high-value chemicals such as cellulose, hemicellulose and lignin. The cellulose content in corn stalks is about 40%, and the lignin content is about 18%. Cellulose is a natural polymer formed by glucose molecules connected by strong chemical bonds. It has excellent physical and chemical stability and is also the main component of wood. Lignin is a high-molecular polymer with a three-dimensional network structure formed by phenylpropane structural units connected by covalent bonds. Its physical and chemical properties are stable. It is worth noting that lignin has strong adhesive properties and can replace traditional organic adhesives in the preparation process of artificial bio-wood to achieve green manufacturing of artificial bio-wood. In addition, combined with advanced chromatographic separation and membrane separation technology, the technical route can be optimized to achieve zero wastewater discharge in the production process, which is of great significance for green industrial production.

[0003] The patent document with application number CN202110487853.2 proposes a method for preparing a non-glue board made of crop straw, by alkali treatment of wheat straw, and modification of the straw with chloroacetic acid and acryloyl chloride, and using hydrogen peroxide as a cross-linking polymerization initiator, and a cross-linking reaction occurs at the moment of hot pressing, thereby preparing a non-glue board. The steps described in the patent use a large amount of organic solvents (N, N-dimethylformamide solution, triethylamine, chloroacetic acid, acryloyl chloride, etc.), and hydrogen peroxide needs to be added as an initiator. Hydrogen peroxide is very likely to cause an explosion due to the rapid temperature rise during the hot pressing process, and the risk factor is high. The patent document with application number 202311380075.2 also proposes a non-glue straw fiber board and a preparation method thereof, which separates the components of the straw raw material by an organic solvent containing a small molecule additive. The organic solvent separates the components of the straw raw material. While separating the components, the small molecule additive activates the dissolved lignin and hemicellulose in situ, and then a one-pot hot pressing method is used to obtain a non-glue board. The patent also uses a large amount of organic solvents, and does not consider the subsequent treatment process of the organic solvents, which will produce a lot of pollution. The current preparation process adopts a simple "one-pot" treatment method, ignoring the effect of the ratio of lignin and cellulose on the final board performance.

[0004] In summary, in the current preparation process of plant straw-free glue-free boards, chemical modification reagents are commonly used to directly modify the plant straw raw materials, and a large amount of organic solvents are required, which has problems such as complex process flow and serious environmental pollution. Summary of the invention

[0005] Based on the above problems existing in the prior art, the present invention proposes a method for green preparation of glue-free artificial board from corn stalks. The present invention first separates and purifies lignin and cellulose from corn stalks; then, optimizes the ratio of lignin and cellulose, uses water as the only solvent, and greenly prepares the artificial board by hot pressing.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] The first object of the present invention is to provide a method for green preparation of glue-free artificial board from corn stalks, comprising the following steps:

[0008] S1. The pretreated corn stalks were crushed, added with water, heated to 80-100°C and softened for 2-4 hours, and then the solid-liquid separation was performed, and the solid phase was washed with hot water at 60-80°C;

[0009] S2. The solid obtained in step S1 is mixed with an acid solution, heated for acid hydrolysis, and then solid-liquid separation;

[0010] S3. The solid separated in step S2 is mixed with an alkaline solution, heated for alkaline treatment, and then solid-liquid separation is performed, and the solid phase is washed with hot water at 60-80°C to obtain a high-content cellulose product;

[0011] S4. The filtrate obtained in step S3 is neutralized with an acid solution, cooled and allowed to stand, and then solid-liquid separation is performed, and the obtained solid is washed with hot water at 60-80°C to obtain a high-content lignin product;

[0012] S5. The cellulose and lignin separated in steps S3 and S4 are mixed in proportion, a proper amount of water is added as a solvent, and hot-pressed to obtain a non-glue artificial board.

[0013] Cellulose and lignin are the main chemical components of plant straw. Cellulose has high molecular weight characteristics and can provide higher mechanical strength. Lignin, as a natural adhesive in plant straw, can effectively bond the components.

[0014] Furthermore, the proportion of water in step S1 is 5-7 times the weight of the raw material.

[0015] In some embodiments, in step S1, the solid phase after solid-liquid separation is washed three times with hot water at 60-80°C;

[0016] In some embodiments of the present invention, the acid solution used in step S2 is a sulfuric acid solution with a mass concentration of 1.5-2.5%, the amount of the acid solution is 2-5 times the mass of the solid, the hydrolysis temperature is 100-130° C., and the hydrolysis time is 1-3 hours.

[0017] In some embodiments of the present invention, the alkaline solution in step S3 is a sodium hydroxide solution with a mass concentration of 1.0-4.0%, the amount of the alkaline solution is 2-5 times the mass of the solid, the insulation temperature is 90-120° C., and the insulation time is 1-3 hours.

[0018] In some embodiments of the present invention, the acid solution in step S4 is a sulfuric acid solution with a mass concentration of 1.5-2.5%.

[0019] In some embodiments of the present invention, in step S5, the proportion of cellulose is controlled to be between 70% and 80%, and the proportion of lignin is controlled to be between 20% and 30%.

[0020] In some embodiments of the present invention, in step S5, the hot pressing temperature is 140-180° C., the hot pressing pressure is 6-10 MPa, and the hot pressing time is 10-30 min.

[0021] Furthermore, the preparation method of the present invention also includes step S6. After the waste liquid generated in steps S1-S4 is neutralized by acid and alkali, a separation system is used to realize water recycling, thereby realizing green production. In step S6, sulfuric acid waste liquid is neutralized with sodium hydroxide waste liquid to prepare Na2SO4 salt byproduct; the overall process finally obtains an artificial bio-board product, while realizing the recycling of waste water in the production process.

[0022] Further, the separation system in step S6 refers to a chromatographic separation system and a membrane separation system;

[0023] In some embodiments, the chromatographic separation system includes anion exchange resin chromatography and cation exchange resin chromatography, and the membrane separation system is a nanofiltration membrane.

[0024] In some embodiments, in step S1, after the pigment, ash and other components in the corn stalks are initially removed, the solid and liquid are separated, and the solid phase is washed three times with hot water at 60-80°C;

[0025] In some embodiments, in step S3, the solid-liquid separation is performed, and the solid phase is washed three times with hot water at 60-80°C;

[0026] In some embodiments, in step S4, the solid and liquid are separated, and the solid phase is washed three times with hot water at 60-80°C.

[0027] The second aspect of the present invention is to provide a glue-free artificial board prepared by the preparation method, wherein the elastic modulus is ≥800MPa.

[0028] The third aspect of the present invention is to provide the application of the glue-free artificial board in temporary buildings and decorations, non-bearing parts of furniture, packaging materials, and experimental materials. Since the board prepared by the present invention does not use organic solvents in the production process, it is green and environmentally friendly and suitable for some application scenarios with tight construction schedules and high environmental protection requirements, such as temporary facilities, enclosures, booths, etc. at exhibitions; or for special groups, such as experimental equipment in schools or educational institutions.

[0029] The present invention has the following beneficial effects:

[0030] (1) The present invention provides a method for preparing a glue-free artificial board from corn stalks. The method uses raw materials of lignin and cellulose, both of which are extracted from corn stalks. The raw materials are widely available and the cost is low.

[0031] (2) The preparation method provided by the present invention uses water as the only solvent in the process, and can realize the hot pressing preparation of glue-free artificial board in a wide temperature range. Compared with the traditional artificial board preparation process that requires the addition of adhesives, the addition of hydrogen peroxide strong oxidant, and the pre-modification of straw components, the present method is simple and more environmentally friendly;

[0032] (3) The preparation method provided by the present invention can neutralize the sulfuric acid waste liquid and the sodium hydroxide waste liquid generated in the process to prepare industrial Na2SO4 salt, and can realize the recycling of water in the whole process without discharging waste water, thereby saving water resources and avoiding pollution.

[0033] (4) The density of the glue-free sheet prepared by the present invention can reach 0.69 g cm -3 , static bending strength reaches 10.5MPa, elastic modulus 1035MPa. It has high application value in some application scenarios with high environmental protection requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings are used to provide a further understanding of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the present application and do not constitute a limitation of the present application. In the accompanying drawings:

[0035] Figure 1 SEM image of cellulose in Example 1;

[0036] Figure 2 Scanning electron microscope (SEM) image of lignin in Example 1;

[0037] Figure 3 The influence of hot pressing temperature on the elastic modulus of the sheet;

[0038] Figure 4 The influence of hot pressing pressure on the elastic modulus of the sheet;

[0039] Figure 5 The effect of hot pressing time on the elastic modulus of the sheet;

[0040] Figure 6 The effect of lignin mass fraction on the elastic modulus of the board;

[0041] Figure 7 This is a photo of the plate prepared in Example 7. DETAILED DESCRIPTION

[0042] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the embodiments of the specification. These embodiments are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually based on conventional conditions or conditions recommended by the manufacturer.

[0043] The following description sets forth many specific details to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. The present invention is not limited to the specific embodiments disclosed below.

[0044] Test method:

[0045] (1) The lignin and cellulose contents were determined according to NY / T 3494-2019 “Determination of Cellulose, Hemicellulose and Lignin in Agricultural Biomass Raw Materials”.

[0046] (2) The relevant properties of the prepared board are measured by the three-point bending method according to the standard GB / T 17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels".

[0047] Example 1

[0048] This embodiment is used for a method for preparing a green glue-free artificial board from corn stalks as follows:

[0049] (1) 1.50 kg of corn stalks were crushed, 8 kg of water was added, and the mixture was heated to 100° C. and kept warm for 3 hours for softening. The solid and liquid were separated, and the solid powder was washed with 80° C. hot water for 3 times to obtain 1.25 kg of solid residue;

[0050] (2) mixing the solid obtained in step (1) with a 2.5% sulfuric acid solution of 5 times the solid mass, heating to 130° C. for hydrolysis for 2 hours, and then performing solid-liquid separation. The obtained solid residue of 0.63 kg is used to extract lignin and cellulose;

[0051] (3) The solid obtained in step (2) was mixed with 4.0% sodium hydroxide solution of 5 times the solid mass, heated to 100° C., and alkali treated for 3 hours, followed by solid-liquid separation. The obtained solid was washed with hot water at 80° C. for 3 times to obtain 0.41 kg of cellulose product with a cellulose content of 91%. The SEM image of the obtained cellulose is shown in FIG. Figure 1 ;

[0052] (4) The filtrate obtained in step (3) was mixed with an excess of 1.5% sulfuric acid solution, cooled and allowed to stand, and then solid-liquid separation was performed. The obtained solid was washed three times with hot water at 80° C. to obtain 0.11 kg of lignin product with a lignin content of 92%. The SEM image of the obtained lignin is shown in FIG. Figure 1 ;

[0053] (5) The sulfuric acid waste liquid generated in the above process is neutralized with the sodium hydroxide waste liquid to obtain Na2SO4 salt. The remaining waste liquid is purified by an anion exchange chromatography column and a cation exchange chromatography column to remove the remaining impurity ions, respectively, and finally recycled through a nanofiltration membrane to regenerate water, which can be used for a new round of extraction.

[0054] Example 2

[0055] This embodiment is used for a method for preparing a green glue-free artificial board from corn stalks as follows:

[0056] (1) 1.50 kg of corn stalks were crushed, 10 kg of water was added, and the mixture was heated to 100° C. and kept warm for 3 hours for softening. The solid and liquid were separated, and the solid powder was washed with 80° C. hot water for 3 times to obtain 1.38 kg of solid residue;

[0057] (2) mixing the solid obtained in step (1) with 2.0% sulfuric acid solution of 3 times the weight of the solid, heating to 110° C. for hydrolysis for 3 hours, and then performing solid-liquid separation. The obtained solid residue of 0.72 kg is used to extract lignin and cellulose;

[0058] (3) mixing the solid obtained in step (2) with 3 times the mass of the solid solution of 2.0% sodium hydroxide, heating to 100° C., alkali treatment for 3 hours, then performing solid-liquid separation, and washing the obtained solid with 80° C. hot water 3 times to obtain 0.51 kg of cellulose product with a cellulose content of 88%;

[0059] (4) mixing the filtrate obtained in step (3) with an excess of 1.5% sulfuric acid solution, cooling and standing, and then performing solid-liquid separation. The obtained solid was washed three times with hot water at 80° C. to obtain 0.16 kg of lignin product with a lignin content of 91%;

[0060] (5) The sulfuric acid waste liquid generated in the above process is neutralized with the sodium hydroxide waste liquid to obtain Na2SO4 salt. The remaining waste liquid is purified by an anion exchange chromatography column and a cation exchange chromatography column to remove the remaining impurity ions, respectively, and finally recycled through a nanofiltration membrane to regenerate water, which can be used for a new round of extraction.

[0061] Example 3 Effect of hot pressing temperature on the plate

[0062] This embodiment is used for a method for preparing a green glue-free artificial board from corn stalks as follows:

[0063] Weigh 20g of lignin and 80g of cellulose obtained in Example 1, add 60g of water, mechanically premix and mix evenly, then evenly spread in a mold with a size of 150mm×150mm×5mm, pre-press at room temperature for 1 minute, then hot press, the hot pressing temperature is 100, 120, 140, 160 and 180℃, the hot pressing pressure is 8MPa, the hot pressing time is 20min, cool and remove the mold, and dry to obtain the artificial biological board. Taking the elastic modulus as the measurement index, the single factor study of the effect of hot pressing temperature on the performance of the board is shown in the following figure. Figure 3 .

[0064] Example 4 Effect of hot pressing pressure on the plate

[0065] This embodiment is used for a method for preparing a green glue-free artificial board from corn stalks as follows:

[0066] Weigh 20g of lignin and 80g of cellulose obtained in Example 1, add 60g of water, mechanically premix and mix evenly, then evenly spread in a mold with a size of 150mm×150mm×5mm, pre-press at room temperature for 1 minute, then hot press, hot press temperature 160℃, hot press pressures of 2, 4, 6, 8 and 10MPa respectively, hot press time 20min, cool and demold, dry to obtain artificial bio-board. Using elastic modulus as a measurement index, the single factor study of the effect of hot press pressure on board performance, the results are shown in Figure 4 .

[0067] Example 5 Effect of hot pressing time on the plate

[0068] This embodiment is used for a method for preparing a green glue-free artificial board from corn stalks as follows:

[0069] Weigh 20g of lignin and 80g of cellulose obtained in Example 1, add 60g of water, mechanically premix and mix evenly, then evenly spread in a mold with a size of 150mm×150mm×5mm, pre-press at room temperature for 1 minute, then hot press, hot press temperature 160℃, hot press pressure 8MPa, hot press time 5, 10, 20, 30 and 40min respectively, cool and demold, dry to obtain artificial biological board. Using elastic modulus as a measurement indicator, the single factor study of the effect of hot pressing time on board performance, the results are shown in Figure 5 .

[0070] Example 6 Effect of lignin mass fraction on board material

[0071] This embodiment is used for a method for preparing a green glue-free artificial board from corn stalks as follows:

[0072] The lignin content was adjusted to 10, 15, 20, 25 and 30% (the total mass of lignin and cellulose was controlled to be 100g), 60g of water was added, the mixture was pre-mixed evenly, and then evenly spread in a mold with a size of 150mm×150mm×5mm, pre-pressed at room temperature for 1 minute, and then hot pressed at a temperature of 160℃, a pressure of 8MPa, and a time of 20min. After cooling and demolding, the artificial bio-board was dried. The elastic modulus was used as a measurement index to investigate the effect of the mass fraction of lignin on the performance of the board. The results are shown in Figure 6 .

[0073] Orthogonal experiment

[0074] Based on the single factor analysis of hot pressing temperature, hot pressing pressure, hot pressing time and lignin mass fraction, a four-factor three-level L9(3 4 ) Orthogonal experiment was performed to optimize the process parameters. The scheme and results are shown in Tables 1 and 2.

[0075] Table 1 Orthogonal experimental factor level table

[0076]

[0077] Table 2 Orthogonal experiment results and analysis

[0078]

[0079] Example 7 Preparation of plate with parameters optimized by orthogonal experiment:

[0080] Weigh 30 g of lignin and 70 g of cellulose obtained in Example 1, add 60 g of water, pre-mix mechanically and mix evenly, then evenly spread in a mold with a size of 150 mm×150 mm×5 mm, pre-press at room temperature for 1 minute, and then hot press at a temperature of 160°C, a pressure of 10 MPa, and a time of 30 min. After cooling, demolding, and drying, an artificial bio-board is obtained.

[0081] The SEM results of corn straw cellulose and lignin in Example 1 are as follows: Figure 1 and Figure 2 As shown. Figure 1 As shown in the figure, the cellulose sample as a whole presents a long fiber-like curly morphology, with a width between 10 and 30 μm and a length greater than 200 μm. The overall fiber morphology is conducive to improving the flexibility and tensile strength of the material.

[0082] like Figure 1 As shown in the figure, the lignin sample is in the form of hollow microspheres with a size of about 10 to 40 μm. Smaller hollow microspheres are beneficial to promoting the accessibility of lignin in cellulose, which helps to more fully and evenly bond cellulose together during the hot pressing process, thereby improving the strength of the final artificial board.

[0083] The results of the orthogonal experiment are shown in Tables 1 and 2. From the R value of the orthogonal experiment results, it can be seen that the order of the influence of the four factors discussed on the strength of the final board is: hot pressing pressure > hot pressing temperature > hot pressing time > lignin mass fraction. From the k value of the orthogonal experiment results, it can be seen that the optimal combination is hot pressing temperature 160℃, hot pressing pressure 10MPa, hot pressing time 30min, and lignin content 30%. According to the above-determined optimization conditions, the density of the prepared artificial board is 0.69g cm -3 , static bending strength is 10.5MPa, and elastic modulus can reach 1035MPa.

[0084] In summary, the present invention discloses a method for green preparation of glue-free artificial board from corn stalks, which belongs to the technical field of comprehensive utilization of straw. Compared with the prior art, the preparation process of the glue-free artificial board of the present invention does not require the addition of any external adhesive or modified chemical reagent. By extracting and separating lignin and cellulose in corn stalks, optimizing the ratio of lignin and cellulose, and using water as the only solvent, the glue-free artificial board with excellent performance can be prepared by hot pressing within a wide temperature range. Effective resource utilization of corn stalks is achieved, and the glue-free artificial board finally prepared has the characteristics of low production cost and no pollution of biological materials. In view of the current market field, the glue-free artificial board prepared by the present invention is expected to become a promising substitute for traditional boards, and it is of great significance to realize the comprehensive utilization of corn stalks.

[0085] The above embodiments are only examples for clearly illustrating the method of the present invention, and are not intended to limit the implementation methods. For those of ordinary skill in the art, other different forms of changes, modifications, substitutions and variations may be made without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing green glue-free artificial board from corn stalks, characterized in that: The steps include: S1. The pretreated corn stalks were crushed, added with water, heated to 80-100°C and softened for 2-4 hours, and then the solid-liquid separation was performed, and the solid phase was washed with hot water at 60-80°C; S2. The solid obtained in step S1 is mixed with an acid solution, heated for acid hydrolysis, and then solid-liquid separation; S3. The solid separated in step S2 is mixed with an alkaline solution, heated for alkaline treatment, and then solid-liquid separation is performed, and the solid phase is washed with hot water at 60-80°C to obtain a high-content cellulose product; S4. The filtrate obtained in step S3 is neutralized with an acid solution, cooled and allowed to stand, and then solid-liquid separation is performed, and the obtained solid is washed with hot water at 60-80°C to obtain a high-content lignin product; S5. The cellulose and lignin separated in steps S3 and S4 are mixed in proportion, a proper amount of water is added as a solvent, and hot-pressed to obtain a non-glue artificial board.

2. The method for preparing green glue-free artificial board from corn stalks according to claim 1, characterized in that: The proportion of water in step S1 is 5-7 times the weight of the raw material.

3. The method for preparing green glue-free artificial board from corn stalks according to claim 1, characterized in that: In step S2, the acid solution is a sulfuric acid solution with a mass concentration of 1.5-2.5%, the amount of the acid solution is 2-5 times the mass of the solid, the hydrolysis temperature is 100-130° C., and the hydrolysis time is 1-3 hours.

4. The method for preparing green glue-free artificial board from corn stalks according to claim 1, characterized in that: In step S3, the alkaline solution is a sodium hydroxide solution with a mass concentration of 1.0-4.0%, the amount of the alkaline solution is 2-5 times the mass of the solid, the insulation temperature is 90-120° C., and the insulation time is 1-3 hours.

5. The method for preparing green glue-free artificial board from corn stalks according to claim 1, characterized in that: The acid solution in step S4 is a sulfuric acid solution with a mass concentration of 1.5-2.5%.

6. The method for preparing green glue-free artificial board from corn stalks according to claim 1, characterized in that: In step S5, the proportion of cellulose is controlled to be between 70% and 80%, and the proportion of lignin is controlled to be between 20% and 30%.

7. The method for preparing green glue-free artificial board from corn stalks according to claim 1, characterized in that: In step S5, the hot pressing temperature is 140-180° C., the hot pressing pressure is 6-10 MPa, and the hot pressing time is 10-30 min.

8. The method for preparing green glue-free artificial board from corn stalks according to claim 1, characterized in that: The method also includes step S6. After the waste liquid generated in steps S1-S4 is neutralized by acid and alkali, a separation system is used to realize water recycling to prepare a Na2SO4 salt by-product.

9. The glue-free artificial board prepared by the preparation method according to any one of claims 1 to 8, characterized in that: Elastic modulus ≥800MPa.

10. Use of the glue-free artificial board according to claim 9 in temporary buildings and decorations, non-bearing parts of furniture, packaging materials, and experimental materials.

Citation Information

Patent Citations

  • Inorganic salt recovery during processing of lignocellulosic feedstocks

    CA2565433A1

  • Pretreatment method of wood fiber raw materials

    CN101864683A

  • Method for separating and extracting lignin from plant straws and comprehensive utilization method of plant straws

    CN110306374A

  • Comprehensive utilization of plant straw and pollution preventing and harnessing method in paper making process

    CN1565761A